Efeitos quânticos em graus de liberdade eletrônicos e fotônicos em dispositivos mesoscópicos caóticos - Vasconcelos, Thiago Conrado de (2020)
In this work we investigate both particle and spin transport in two dierent devices. In particle transport we will investigate the correlation measurement and the weak location for the Hanbury-Brown Twiss Chaotic Eect in mesoscopic systems. In spin transport we have as main interest to calculate the universal uctuation of parameter IREE in the Inverse Hall Eect of Spin. This parameter measures the conversion of spin current into charge current, we will calculate its uctuation in a chaotic quantum point with chiral symmetry at low temperatures and in the metallic regime. To perform the calculations of the correlation in the chaotic HBT eect, as well as the calculation of the parameter uctuation, we use the theory of random matrices, the diagrammatic method and its expansion. Along the calculations the correlation of the particles we show that there is an antibunching of bosons even though the reection amplitude is the same as the transmission amplitude in the apparatus. We show that the eects of quantum interference between particles are neglected when we apply the magnetic eld in the metallic regime and in hybrid metal/superconducting systems, moreover we show that for chiral regimes, there is no suppression of quantum interference between the particles even with the magnetic eld turned on. We also calculated the uctuation of parameter in the metallic regime and showed that it uctuates between 0.11 to 0.33 on the nanometer scale depending on the analyzed system. This result is in line with experimental articles in the area and if we look at the chiral regime we nd the order of uctuation is about 10 nanometers, in which the value is also in line with recent experimental results in the area.